Continuation, imbrications et écarts : liens entre la défense des droits LGBTQI+ et la lutte contre le VIH/sida en Tunisie - Marta Luceño Moreno (L’Année du Maghreb)
In Tunisia, as in other countries in the region, the spaces for the fight against HIV/AIDS have been places of socialization, training and network development for LGBTQI+ people. However, after the 2011 revolution, a reconfiguration of activist spaces emerged, with the birth of associations and collectives that defend the LGBTQI+ cause with a more identity-based approach. The latter coexist with associations fighting against HIV/AIDS, which emphasize a public health approach. The article will examine the tensions and gaps between these two poles, as well as their overlaps.Based on interviews conducted between 2018 and 2020 with leaders and members of associations or organisations in Tunisia, the author discusses two distinct moments: the first relates the history of the fight against HIV/AIDS before the 2011 revolution; the second explores the post-revolutionary relationship between the movement against HIV/AIDS and the LGBTQI+ community. Indeed, the context of democratic transition and the involvement of international donors who finance the LGBTQI+ cause, has allowed for greater identity affirmation. This relative visibility is easier to grasp in the capital than in the rest of the country, but everywhere, negociations are occuring between the various associations who continue to fight for greater information in order to curb the HIV/AIDS epidemics.